HEAT AND MASS TRANSFER FOR COOLING OF AIR BY EVAPORATIVE PROCESS - Hien, Le Van; Thanh, Nguyen Thi Tam (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Air conditioning systems are responsible for increasing men's worke efficiency as well for his comfort, mainly in the warm periods of the year. Currently, the most used system is the mechanical vapor compression system. Furthermore, the higher electricity demand for cooling causes summer peaks, which may lead to high electricity prices and grid connected problems as black-outs. However, in many cases, evaporative cooling system can be an alternative to replace the conventional system, under several conditions, or as a pre-cooler in the conventional systems. Also the remaining cooling demand must be covered with alternative, environmentally friendly cooling technologies. Evaporative cooling operates using induced processes of heat and mass transfer, where water and air are the working fluids. It consists in water evaporation, induced by the passage of an air flow, thus decreasing the air temperature. This paper presents the basic principles of the evaporative cooling process for human thermal comfort, the principles of operation for the direct evaporative cooling system and the mathematical development of the equations of thermal exchanges, allowing the determination of the effectiveness of saturation to determine the convective heat transfer coefficient and to compare with the mathematical model.